Production of monoclonal antibodies that recognize specific and cross-reactive antigens of Fusobacterium nucleatum. - Bird, P S (1987)
Monoclonal antibodies (MAbs) against the cell surface antigens of Fusobacterium nucleatum 263 were obtained by fusion of murine myeloma cells (P3-NSI/1-Ag4-1) with the splenocytes of BALB/c mice immunized with whole cells of F. nucleatum 263. Screening was performed using an enzyme-linked immunosorbent assay (ELISA) against the immunizing strain, F. nucleatum 263. Further selection was done using a bacterial panel consisting of Bacteroides, Actinomyces, Streptococcus, Fusobacterium, and Escherichia species. Twelve MAbs were selected on the basis of this screening procedure, seven of which reacted specifically with F. nucleatum 263. Two reacted with F. nucleatum 263 and ATCC 25586, and three reacted with F. nucleatum 263, ATCC 25586, and UQD-003 (a clinical isolate) and also cross-reacted with Fusobacterium russii ATCC 25533. The selected MAbs were then further characterized by absorption experiments with suspensions of intact whole bacterial cells, and the residual binding activity of the supernatants was determined in an ELISA. To determine whether the MAbs reacted with the same or different epitopes, pairs of MAbs were reacted together and independently in a checkerboard manner in an ELISA. The additive or nonadditive nature of the reactivity was determined. A competitive inhibition assay was performed using one labeled and selected unlabeled MAbs. The results of these experiments suggested some epitope sharing among the selected MAbs that reacted with a specific antigen on F. nucleatum and also shared cross-reactive antigens with the three strains of F. nucleatum and F. russii.